Sistema web para la gestión de las actividades de servicio a la comunidad en el área de vinculación con la sociedad de la Facultad de C.I.Y.A - Amores Lema, Byron Enrique (2017)
In the Relationship with society area at Technical University of Cotopaxi, there wasn't any type of computer system, considering that students wanted to get information and an response immediately about it, instead students, coordinators and tutors wanted a greater agility in the management of the service activities in a community, mainly, students carried out it face-to-face or in the case of tutors carried out through the use of electronic sheets, text editors, etc., taking into account that the information files could get lost or there would be redundancy in it. Therefore, the project purpose was to strengthen the management of community service activities in the area of Relationship with society of C.I.Y.A. faculty, through a Web System for the development and implementation that allowed students, coordinators and tutors to speed up the information handling, preventing it becomes an useful information, the system helped to ensure that there wasn't duplication of data and handling times aren't slow it helped to get organized and correct information. Providing a security and confidence to who manipulates it. The deductive hypothetical method was used since it was argued that the manipulation of traditional means such as printed sheets, Office tools, and filing cabinets are the only students, tutors and coordinators´ resources for the management of the community service activities, causing the process doesn't have an optimized time. For the Web System development the methodology of software SCRUM development was used because it is mainly focused on the development and it is a process in which a set of good practices are applied in a regular way to work collaboratively in a team and obtain the best result in a project in which the web system was divided into 5 modules such as User Registration, Administration, Enrolment-Evaluations, files and Events-Certificates. The beneficiaries of the technological proposal were mainly students, tutors and coordinators of C.I.Y.A Faculty at Technical University of Cotopaxi.